Design and measurement of a tiny wideband antenna for deeply embedded biomedical devices - Al Gburi, Ahmed Jamal Abdullah; Bousrout, Abdelmouttalib; Khabba, Asma; Ullah, Atta; Ibnyaich, Saida; Mazri, Tomader; Habibi, Mohamed (IOP Publishing Ltd, 2025)
The increasing demand for compact and efficient implantable medical devices has driven the development of advanced antenna solutions for biomedical applications. This study presents a novel wideband implantable antenna specifically tailored for scalp implantation, operating across two critical frequency ranges: the Industrial, Scientific, and Medical (ISM) band (2.4–2.48 GHz) and the midfield frequency range (1.45–1.6 GHz). The antenna’s compact design, with overall dimensions of 3 × 4 × 0.5 mm3, features a 0.25 mm thick dielectric layer constructed from Rogers 4350B (εr= 3.66, tanδ = 0.0031)for both the substrate and superstrate. Innovative design elements, including openended slots in the radiating patch and closed-ended slots in the ground plane, contribute to its compact size, enhanced impedance matching, and improved bandwidth performance. The antenna achieves a peak gain of −19.92 dBi at 2.45 GHz and delivers an ultra-wide bandwidth of 1836.8 MHz, spanning from 1.0602 GHz to 2.8970 GHz. These characteristics ensure reliable operation in diverse implantation scenarios within the human body, while adhering to IEEE C95.1-2005 safety standards for specific absorption rate (SAR) compliance. Comprehensive performance evaluations were conducted using finite-element simulations in homogeneous tissue environments, employing HFSS and CST software. The simulated results aligned closely with experimental measurements, validating the design’s accuracy and manufacturability. Additionally, a link budget analysis confirmed the antenna’s ability to maintain a robust and reliable wireless telemetric connection, demonstrating its suitability for medical applications and ensuring safe, efficient communication.